Kemampuan Guru Dalam Penggunaan Instrumen Penilaian Portofolio Dalam Pelaksanaan Supervisi Administrasi Di SMA Negeri 1 Padang Bolak Julu - Hadi Daud Siregar (Pusat Riset dan Inovasi Nasional, 2023)
This school action research started with the problems faced by teachers of SMA Negeri 1 Padang Bolak Julu in carrying out learning evaluations. In conducting evaluations, teachers rarely use portfolio assessment. In fact, in learning that requires mastery of the material as well as the possession of good skills and attitudes, it would be better if an assessment instrument was used which provides opportunities for students to demonstrate their ability to solve problems, reason, communicate, conduct investigations, and be creative. The author as a school coach tries to provide assistance to teachers in using portfolio assessment instruments. The purpose of this research is to improve the teacher's ability to use portfolio assessment instruments. This type of research is action research using a qualitative approach. The research data is in the form of information about the process and action data obtained from observations, assessment results, discussions and documentation. The data source is the process of carrying out supervision activities at SMA Negeri 1 Padang Bolak Julu. Data analysis was performed using a qualitative data analysis model. Based on the results of the research, the supervision activities carried out were able to improve and contribute to improving the teacher's ability to use portfolio assessment instruments. This result can be seen from the assessment of the teacher's ability which has increased, namely in the first cycle the percentage of the average score obtained by the teacher was 72.5%, meaning that the teacher's pedagogical competence in this cycle was still in the sufficient category, while in cycle II, the percentage of the average score was the average obtained by the teacher increased to 87.5%, meaning that the teacher's ability to use portfolio assessment instruments in cycle II was in the good category. Thus it can be interpreted that supervision activities can improve teachers' abilities in using portfolio assessment instruments at SMA Negeri 1 Padang Bolak Julu.